2023
DOI: 10.3390/polym15163414
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Bast-Fibre-Reinforced Hybrid Composites and Their Applications

Abstract: The development of eco-friendly products to protect the environment has become a topical subject in the research and industrial communities. This is a result of strict environmental regulations necessitating the development of novel strategies to reduce our reliance on petroleum-based products, which exert a negative effect on our ecosystem. Bast-fibre-based hybrids have been extensively studied for various applications due to their eco-friendliness and cost effectiveness. There is a very limited number of rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
(330 reference statements)
0
1
0
Order By: Relevance
“…While increasing the snail shell powder content, the hardness values also simultaneously increase. Simultaneously, surface roughness and chemical reactivity of the roselle fibers are improved by the mercerization process, which increase the interfacial bonding between the fibers and the epoxy resin [36]. The robust interfacial bond confirms distribution of stress evenly and load transfer.…”
Section: Hardness Behaviour Of Laminatesmentioning
confidence: 87%
“…While increasing the snail shell powder content, the hardness values also simultaneously increase. Simultaneously, surface roughness and chemical reactivity of the roselle fibers are improved by the mercerization process, which increase the interfacial bonding between the fibers and the epoxy resin [36]. The robust interfacial bond confirms distribution of stress evenly and load transfer.…”
Section: Hardness Behaviour Of Laminatesmentioning
confidence: 87%
“…Furthermore, the potential for these composites to be recycled or biodegraded aligns with the increasing legislative pressures for sustainable materials solutions [5]. Industrial applications of bast fiber composites have been expanding, with research investigations showcasing their use in automotive, aerospace, packaging, and construction sectors [6][7][8]. Recent studies have demonstrated that with appropriate treatment and manufacturing techniques, bast fibers can exhibit compatibility with various polymeric matrices, resulting in composites that meet, if not exceed, the performance of conventional materials [9,10].…”
Section: Introductionmentioning
confidence: 99%